Language Assessment Literacy of Middle School English Teachers in Mexico - Analynn Bustamante (Languages, 2022)
Because English is an integral component of education in Mexico, it is necessary to explore teachers’ language assessment literacy (LAL), or their language assessment knowledge and practices. Previous LAL studies have been performed in standardized testing-focused. However, the present study aims to explore the LAL of teachers of middle school English students in a context where governmental policies strive to engender communicative language learning, specifically, Mexico. I have taken a mixed methods approach which involved a survey (N = 123) and interviews at two locations in Mexico. The semi-structured interviews were conducted at one bilingual middle school (N = 7) and in one extracurricular English program (N = 6). Participants were asked about their previous training, confidence levels in their assessment practices, and their training needs. Findings suggest a divide among teachers with higher and lower levels of LAL. Participants indicated that their training primarily covered traditional forms of assessment and classroom-level decision-making. However, data also suggest that participants valued non-traditional assessment activities. Finally, participants desired training on topics such as the use of technology in assessment, unfamiliar non-traditional assessment activities, and program-level decision-making.